wheat sowing depth in the cerrados region. I. Seedling emergence - Silva, Dijalma Barbosa da (Pesquisa Agropecuaria Brasileira, 1992)
The sowing depth is a crucial factor in determining the wheat grain yield. The objective of this study was to evaluate the sowing depth on grain yield of irrigated wheat (Triticum aestivum L.) in the Cerrados region. The field study was conducted in Planaltina, DF, Brazil, in 1990. The treatments were four sowing depths (2.0; 5.0; 8.0 and 11.0 cm) and five cultivars (BR 10; BR 12; BR 33; Anahuac and Candeias). No effect of the sowing depth was observed on the grain yield, initial stand, number of spikes/m2, hectoliter weight, and 1000-grain weight. However, a relative decrease of 7.13; 7.36 and 3.90% was observed in the grain yield in the 2.0 cm depth of sowing when compared with the sowing depths of 5.0; 8.0 and 11.0 cm, respectively. The grain yield was similar for all cultivars. Nevertheless, the behavior of the cultivars were different with respect to the other parameters evaluated in this study.